A new species of tiger beetle (Coleoptera: Cicindelidae) from the Death Valley ecosystem - Duran, Daniel P.; Chambers, Aaron W.; Nelson, Kristie N.; Roman, Stephen J. (Zootaxa, 2023)
A new tiger beetle species, Cicindela timbisha Duran, Chambers, Nelson & Roman n. sp., of the tribe Cicindelini, is described from the Death Valley ecoregion of eastern California, USA. It is most similar to C. senilis G.Horn, 1866 but is distinguished on the basis of multiple morphological characteristics, including differences in maculations, chaetotaxy of the antennae and a statistically significant difference in body size (P<0.001). The new species also differs from C. senilis in that it is found in an isolated freshwater spring in an inland basin east of the Sierra Nevada mountains, whereas C. senilis is found in saline soils, primarily coastal areas and inland plains, west of the Sierra Nevada range.